Can an outpatient risk assessment tool predict who needs postoperative haemoglobin monitoring?. (1st January 2021) - Nikolaus, Oliver B.; Rowe, Taylor; Springer, Bryan D.; Fehring, Thomas K.; Martin, John R.
Abstract : Aims: Recent improvements in surgical technique and perioperative blood management after total joint replacement (TJR) have decreased rates of transfusion. However, as many surgeons transition to outpatient TJR, obtaining routine postoperative blood tests becomes more challenging. Therefore, we sought to determine if a preoperative outpatient assessment tool that stratifies patients based on numerous medical comorbidities could predict who required postoperative haemoglobin (Hb) measurement. Methods: We performed a prospective study of consecutive unilateral primary total knee arthroplasties (TKAs) and total hip arthroplasties (THAs) performed at a single institution. Prospectively collected data included preoperative and postoperative Hb levels, need for blood transfusion, length of hospital stay, and Outpatient Arthroplasty Risk Assessment (OARA) score. Results: A total of 504 patients met inclusion criteria. Mean age at time of arthroplasty was 65.3 years (SD 10.2). Of the patients, 216 (42.9%) were THAs and 288 (57.1%) were TKAs. Six patients required a blood transfusion postoperatively (1.19%). Transfusion after surgery was associated with lower postoperative day 1 Hb (median of 8.5 (interquartile range (IQR) 7.9 to 8.6) vs 11.3 (IQR 10.4 to 12.2); p < 0.001), longer length of stay (1 day (IQR 1 to 1) vs 2 days (IQR 2 to 3); p < 0.001), higher OARA score (median of 60.0 (IQR 40 to 75) vs 5.0 (IQR 0-35); p = 0.001), and total hip arthroplasty (p < 0.001). All patients who received a transfusion had an OARA score > 34; however, this did not reach statistical significance as a screening threshold. Conclusion: Risk of blood transfusion after primary TJR was uncommon in our series, with an incidence of 1.19%. Transfusion was associated with OARA scores > 60. The OARA score, not American Society of Anesthesiologists grade, reliably identified patients at risk for postoperative blood transfusion. Selective Hb monitoring may result in substantial cost savings in the era of cost containment. Cite this article: Bone Joint J 2021;103-B(1):65–70.